Growth, subject areas, and application of research methods in user studies: A content analysis of articles produced by Pakistani authors - Ullah, Ahsan; Ameen, Kanwal (Journal of librarianship and information science, 2023)
Information science profession is concerned with information user and every development in this field has been designed to make it easier for the user to access documents or information. The current study examined user studies to provide understanding about the users, growth in user studies, topics, and methods of user studies. A content analysis method has been adopted and empirical research articles produced by Pakistani authors during the period 2001–2016 have been examined. Out of 518 empirical articles, 185 user studies were selected for examining users, subject and methods. Growth in user studies research was lower from the period 2001 to 2008 but number of studies increased significantly after 2008. Dominant majority of user studies collected data from educational institutions. Academicians and students were the most frequently studied users. Bureaucrats, judges, and other officials have not been examined for elicitation of their needs in spite of the fact that libraries have been established with government departments and courts. In respect of research areas of user studies, information needs and seeking behavior, use and skills of internet and social media, use of electronic resources and satisfaction of users with library services constitute 90% of user studies research. With respect to use of research methodology, quantitative approach (78%) is popular in user studies followed by mixed methods (10%), qualitative (8%), and multimethod (4%). More than one method is used in 14% user studies research. In case of frequency of research methods, questionnaire (72%) is the dominant method followed by interview (14%). The current study is unique because it identified popular topics and methods in user studies research.